Evocações históricas do liberalismo em Raul Brandão - Lage, Otília (2020)
The purpose of this article, in the context of the celebration of centenarians, is to reflect, crossing historical and literary studies on the singularity they bring to the contemporary historiographic discourse of Portuguese liberalism, the works of historical matrix and modernity of the writer Raul Brandão, intellectual of transition and rupture between two centuries, which continue to challenge us today. It focuses, in an interdisciplinary perspectve, on the Brandonian corpus of historical component and documentary rigor. El -rei Junot, 1817-Gomes Freire de Andrade, and Preface and Notes to O Siege of Porto, published works between 1912 and 1915, a stage of literary and civic maturity of the author, which involve political-military events of social relevance in the construction of our liberalism, a troubled historical of affirmation of freedoms. The analyzed corpus proves in a rigorous and detailed way, the innovative idea of writing and historical worldview of the writer from Porto, constituting a good contribution to the study of Raul Brandão's work and liberalism itself.